Microencapsulation of Xanthone extracted from Garcinia Mangostana pericarp using freeze drying / Ummi Kalthum Ibrahim... [et al.] - Ibrahim, Ummi Kalthum; Jerry, Timothy Alvin; Maqsood ul-Haque, Siti Noor Suzila; Abd Hashib, Syafiza; Abd Karim, Siti Fatma (Universiti Teknologi MARA Shah Alam, 2019)
Garcinia mangostana fruit is one of the most popular fruit and known as a tropical fruit that has high nutrition value and widely cultivated in the tropical rainforest of some Southeast Asian nations. The main objectives of this research were to identify the composition of extracted xanthones and to determine the antioxidant activity, total phenolic content, moisture content and antimicrobial activity of encapsulated Garcinia mangostana pericarp. Encapsulation process was done by using freeze drying technique. Antioxidant activity, total phenolic content, moisture content and antimicrobial activity of encapsulated xanthones analysis were conducted. The amount of xanthones was detected at range of 515 to 4000 cm⁻ 1 through Fourier transforms infrared spectroscopy (FTIR). The highest value of radical scavenging activity for non-encapsulated xanthones was 82.69% whereas 88.01% for encapsulated xanthones. The total phenolic content (TPC) was found 5.240 mg GAE/g and 6.359 mg GAE/g for non-encapsulated and encapsulated samples, respectively. In conclusion, ncapsulated xanthones from Garcinia mangostana pericarp has high antioxidant activity and antibacterial properties which has potential to the manufacturing functional food, cosmeceutical and pharmaceutical industries.